Pengenalan dan Penerapan Literasi Budaya melalui Program Campus On Duty (CoD) - Farida Nurlaila Zunaidah; Nitya Santi, Novi; Sahari, Sutrisno; wahyudi, wahyudi; Primasatya, Nurita; Fahmi Imron, Ilmawati; Eka Putri, Kharisma; Violina Afya', Zahara (Universitas Nusantara PGRI Kediri, 2023)
Since the establishment of the Covid-19 pandemic alert, the government has made recommendations to carry out all activities at home, including teaching and learning activities in schools. Home learning that is carried out online using a mobile phone has the effect of gadget addiction on children. This has an impact on patterns of social interaction in children which have an effect on lowering cultural literacy in children. Based on this problem, the COD (Campus On Duty) TEAM is trying to assist the implementation of cultural literacy in several schools in the Kediri district. The PKM program activities include 4 stages, namely the preparation, implementation, program evaluation, and reporting stages. The target to be achieved is the application of cultural literacy through simple activities and traditional games to rebuild students' patterns of social interaction. The result of this PKM is cultural literacy assistance which has been carried out in several schools in the Kediri district